Study on Activity and Stability of Native and Chemical Modified Bromoperoxidase - Jirasak Kongkiattikajorn; Pintip Ruenwongsa (Agriculture and Natural Resources, 2006)
Chemical modification of enzymes is widely used as a tool for studying localization of individual amino acids, their participation in the maintenance of the native conformation and for their catalytic activity and stabilization. In this study, two isozymes of bromoperoxidase (BPO); BPOI, BPOII; were isolated and purified from Gracilaria sp. using fast protein liquid chromatography (FPLC) method. The isozymes were characterized and modified by various chemical modifying reagents. The effects of the chemical modification on catalytic activity and stability of BPOI were studied. BPOI was inhibited by 2-hydroxy-5-nitrobenzyl bromide (HNBB), 2-nitrophenylsulfenyl chloride (NPS), N-bromosuccinimide (NBS) and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC). The amino groups of the enzyme were modified with iodoacetamide to change the enzyme’s structure character and to increase its hydrophobicity. This modification improved the enzyme specific activity and increased the thermostability. Chemical modification suggested involvement of Trp, Asp/Glu in the catalytic site of the enzyme due to the decrease of enzyme activity of the modified enzyme. The 2, 4, 6-trinitrobenzenesulfonic acid modification increased the catalytic activity and the iodoacetamide- modified BPOI also showed greater thermal stability and catalytic activity. The improvements of catalytic properties are related to the changes of the hydrophobicity of substituted groups of lysine residues of BPOI.